STUDY OF MAHESH DATTANI’S CULTURAL IDENTITIES - Satendra Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
Culture is the way of life of a community or a social group of people or a clan etc., as well as their common beliefs and practices, according to an anthropological definition of the term, which simplifies a word with a meaning that is otherwise rather complicated. Members of the same culture make sense of the world or interpret it in a manner that is virtually identical to how other members of their culture do so. In other words, they realize and interpret the world around them in practically the same way. But it goes without saying that even within the confines of a single culture, there will be a wide range of emotions, ideas, and thoughts, and it is quite probable that all of these things are susceptible to being interpreted in a variety of different ways. The idea behind culture, on the other hand, is that it organizes and governs the social practices of its members, as well as having a significant impact on how those members behave by shaping them in line with the culture's rules and mandates. The particular meanings that objects take on depend entirely on the one who is doing the interpreting. The manner in which we conceptualize and categories things, as well as the values we ascribe to them, all contribute to the meanings that we assign to the objects that we represent. Participants of the same culture are considered to be a part of the same cultural circuit, and as a result, they share the same cultural codes. These cultural standards frequently play a role in the construction or conception that we do of something that actually exists in the real world, and as a result, the way that we portray that item to ourselves.